Brainstorming, Activating, Reinforcing And Applying (BARA) To Upraise Students’ Reading Comprehension - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; Dewa Gede Agung Gana Kumara (International Journal of Linguistics and Discourse Analytics, 2022)
Reading is part of the process self-development education so that they have the ability to think rationally and academic achievement. Reading comprehension is a reading activity that is directed to gain an understanding of the reading content. This study made use of a classroom action research design with two cycles of learning activities to improve students' reading comprehensions through BARA strategy. Data were collected through pre-test, post-test, and questionnaire. The results showed that the reading comprehensions of the students improved significantly from the first and second cycles when compared to the results of the pre-test. Therefore, the BARA strategy is considered very effective for teaching reading comprehension. This study implies that teachers should consider using BARA strategy to improve students' reading comprehension